Prognostic factors for advanced‐stage human immunodeficiency virus‐associated classical Hodgkin lymphoma treated with doxorubicin, bleomycin, vinblastine, and dacarbazine plus combined antiretroviral therapy: A multi‐institutional retrospective study. Issue 3 (23rd September 2014) - Castillo, Jorge J.; Bower, Mark; Brühlmann, Jérémy; Novak, Urban; Furrer, Hansjakob; Tanaka, Paula Y.; Besson, Caroline; Montoto, Silvia; Cwynarski, Kate; Abramson, Jeremy S.; Dalia, Samir; Bibas, Michele; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The treatment and outcomes of patients with human immunodeficiency virus (HIV)‐associated Hodgkin lymphoma (HL) continue to evolve. The International Prognostic Score (IPS) is used to predict the survival of patients with advanced‐stage HL, but it has not been validated in patients with HIV infection. METHODS This was a multi‐institutional, retrospective study of 229 patients with HIV‐associated, advanced‐stage, classical HL who received doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) plus combination antiretroviral therapy. Their clinical characteristics were presented descriptively, and multivariate analyses were performed to identify the factors that were predictive of response and prognostic of progression‐free survival (PFS) and overall survival (OS). RESULTS The overall and complete response rates to ABVD in patients with HIV‐associated HL were 91% and 83%, respectively. After a median follow‐up of 5 years, the 5‐year PFS and OS rates were 69% and 78%, respectively. In multivariate analyses, there was a trend toward an IPS score >3 as an adverse factor for PFS (hazard ratio [HR], 1.49; P=.15) and OS (HR, 1.84; P=.06). A cluster of differentiation 4 (CD4)‐positive (T‐helper) cell count <200 cells/μL was associated independently with both PFS (HR, 2.60; P=.002) and OS (HR, 2.04; P=.04). The CD4‐positive cell count was associated with an increased incidence of death from other causes (HR, 2.64; P=.04) but not with death from HL‐related causes (HR, 1.55; P=.32). CONCLUSIONS The current results indicate excellent response and survival rates in patients with HIV‐associated, advanced‐stage, classical HL who receive ABVD and combination antiretroviral therapy as well as the prognostic value of the CD4‐positive cell count at the time of lymphoma diagnosis for PFS and OS. Cancer 2015;121:423–431. © 2014 American Cancer Society.